PENGEMBANGAN KUESIONER KEBUTUHAN DAN HAMBATAN PENERAPAN ETIKET OBAT BERBASIS BRAILE - Siti Zamilatul Azkiyah; Aqidatun Naffiah Choirunniza (Jurnal Farmamedika (Pharmamedika Journal), 2024)
Indonesia has around 1.5% or more than 3.75 million blind people. Of concern is that people with visual impairment are at high risk of medication errors. Even though there are many solutions for implementing Braille labels in daily practice, there are not many agencies that provide this service. Therefore, it is necessary to have an instrument that can measure the needs and barriers to implementing Braille etiquette. The research includes developing an instrument to measure the needs and barriers to implementing Braille etiquette in pharmaceutical services. The research instrument developed was a questionnaire with the name EKREB, which is an acronym for "Evaluation of Braille Etiquette Needs and Barriers". The development of the questionnaire went through the instrument design stages which included planning, construction, reliability testing and validity testing. The total number of EKREB questionnaire design items was 23 items which were then distributed online. The testing involved 30 respondents consisting of 11 undergraduate pharmacy students, 8 pharmaceutical technical staff, and 11 pharmacists in the Situbondo area. Of the 20 items tested, the Crobach's Alpha value obtained was 0.908 (0.6) so a decision could be made that the questionnaire was declared reliable and entered the high reliability category. The results of the Pearson Product Moment test have a sig value. From each questionnaire item obtained 0.05 so that the questionnaire items are declared valid. Based on the research results that have been obtained, it can be concluded that the results of the development of the EKREB questionnaire are declared as valid and reliable instruments to be used as data collection tools for evaluating needs and barriers to service implementation. Braille labels in clinical-community pharmacy practice.